Strategy-proof and Symmetric Social Choice Functions for Public Good Economies - Serizawa, Shigehiro (Econometrica, 1999)
We study economies with one private good and one pure public good, and consider the following axioms of social choice functions. Strategy-proofness says that no agent can benefit by misrepresenting his preferences, regardless of whether the other agents misrepresent or not, and whatever his preferences are. Symmetry says that if two agents have the same preference, they must be treated equally. Anonymity says that when the preferences of two agents are switched, their consumption bundles are also switched. Individual rationality says that a social choice function never assigns an allocation which makes some agent worse off than he would be by consuming no public good and paying nothing. In Theorem 1, we characterize the class of strategy-proof, budget-balancing, and symmetric social choice functions, assuming convexity of the cost function of the public good. In Theorem 2, we characterize the class of strategy-proof, budget-balancing, and anonymous social choice functions. In Theorem 3, we characterize the class of strategy-proof, budget-balancing, symmetric, and individually rational social choice functions.